Acidentes e Intoxicações: Estudo numa população do Norte de Portugal - Oliveira, A. (2011)
Grupo Coordenador: Abílio Oliveira, Emídio Carreiro, Conceição Casanova, Virginia Monteiro, Nilza Ferreira, Carla Meireles Grupo de Trabalho: H Amarante – Manuel Reis; H Padre Américo – Abílio Oliveira, Cláudia Monteiro, Eunice Moreira, Grupo Triagem Manchester; CH Póvoa – Conceição Casanova, Conceição Fernandes, Elisabete Coelho, Conceição Silva, Paulo Ferreira, Margarida Pontes, Resende Martins, Silva Pereira, Célia Madalena, Venília Benta, Patrícia Santos, Sandra Ramos, Carlos Sistelo; H Barcelos – Sandra Rocha, Ana Reis, Carla Carvalho, Catarina Sousa, Goreti Lobarinhas; H Chaves – Reis Morais; H S João – Emídio Carreiro, Rute Vaz, Isabel Loureiro, Mafalda Sampaio, Mª Céu Espinheira, Susana Soares, Carla Dias, Paulo Soares, Henrique Soares; H Bragança – Judite Marques, Manuela Ferreira, Rosa Mansano; H S Tirso – Álvaro Sousa; H Guimarães – Carla Meireles, Carla Laranjeira, Carla Costa, Cláudia Neto, Ana Teixeira, Susana Soares, Maria José Vale, Joana Neves, Ana Paula Fernandes, Liliana Macedo, Filipe Oliveira; H Oliveira Azeméis – Virginia Monteiro; CH Vila Real – Nilza Ferreira; H Braga – Carla Moreira, Gabriela Pereira; H Lamego – Jorge Sousa;